UNSTEADY NON-NEWTONIAN FLUID FLOW PROBLEM IN PLANESOLVING BY MAC METHOD - Hussein, Mohammed (Iraqi Journal of Science, 2024)
In this paper consideration is given to viscose, incompressible, time-depended andnon-Newtonian fluid flowing in a straight pipe with square cross-section under theaction of pressure gradient. In particular consideration is given to second order fluidflow which can be represented by the equation of state of the form: 212 4kij ij ik kj T  e  e e i,j = 1,2Where η viscosity coefficient and ζ is normal stress coefficient and, Tij and eij , i,j =1,2are the stress and rate of strain respectively. Cartesian coordinate system has been usedto describe the fluid motion and it is found that equations of motion are controlled byReynolds number and non-Newtonian parameter. The motion equations are solved by anexplicit method namely MAC. Our study is ended with studying the effect of Reynoldsnumber and non-Newtonian parameter on the fluid